Perception of Faces and Elaboration of Gender and Victim/Aggressor Stereotypes: The Influence of Internet Use and of the Perceiver’s Personality - Bracci, Margherita; Guidi, Stefano; Marchigiani, Enrica; Masini, Maurizio; Palmitesta, Paola; Parlangeli, Oronzo (Frontiers in Psychology, 2021)
The use of social media, particularly among youngsters, is characterized by simple and fast image exploration, mostly of people, particularly faces. The study presented here was conducted in order to investigate stereotypical judgments about men’s and women’s faces concerning past events of aggression perpetrated or suffered by the person whose face is viewed, and gender-related differences in the judgments. To this aim, 185 participants answered to a structured questionnaire online. Participants were either university students and workers or high school students which, respectively, completed the questionnaire in university premises or their classrooms. The questionnaire contained 30 photos of young people's faces, 15 males and 15 females (Ma et al., 2015) selected on the basis of the neutrality of their expression, and participants were asked to rate each face with respect to masculinity/femininity, strength/weakness and having a past of aggression, as a victim or as a perpetrator. Information about the empathic abilities and personality traits about participants were also collected. The results indicate that the stereotypes – both of gender and those of victims and perpetrators – emerge as a consequence of the visual exploration of faces that present no facial emotion. Some characteristics of the personality of the observers, such as neuroticism, extraversion, openness, conscientiousness and affective empathy, have a role in facilitating or hindering stereotype processing, in different ways for male and female faces by male and female observers. In particular, both genders attribute to same-gender faces their positive stereotypical attributes - males see males as stronger, masculine and more aggressive than females do, and females see females as more feminine, less weak and less victims than males do. Intensive use of social media emerges as a factor that could facilitate the expression of some stereotypes of violent experiences and considering female subjects as more aggressive. Findings in this study can contribute to research on aggressive behavior on the Net and improve our understanding of multiple factors involved in the elaboration of gender stereotypes relative to violent or victim behavior.